2013
DOI: 10.1597/11-126
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Perception of Hypernasality and Social Judgments in School-Aged Children

Abstract: Purpose : This study investigated both the ability of children to rate nasality and the relationship of those ratings to expert ratings and social acceptance judgments. Method : A total of 10 speech samples were judged for nasality by 44 children ranging in age from 8 to 11 and by an expert judge. Listeners rated nasality on a 3-point response scale. The peer listeners also made five social acceptance ratings about each speaker. Results : Kappas for interrater reliability were moderate to substantial. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 8 publications
2
24
0
3
Order By: Relevance
“…The use of personal criteria may also explain the intrarater agreement obtained in the first (11,14) . That is one of the reasons that led some clinicians and researchers to support the use of prior listener training as a strategy to increase the reliability of auditory perceptual assessments (14,18,24) . Several programs of training have been documented in literature, mostly with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…The use of personal criteria may also explain the intrarater agreement obtained in the first (11,14) . That is one of the reasons that led some clinicians and researchers to support the use of prior listener training as a strategy to increase the reliability of auditory perceptual assessments (14,18,24) . Several programs of training have been documented in literature, mostly with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Negative stereotyping, due to communication disorders, is of high importance to society, since it may cause psychological, educational, and employment disadvantages (Lee et al, 2016). Also in children negative attitudes toward peers with speech impairments have been observed and subjective perceptions of speech have been related to social acceptance (Blood & Hyman, 1977;Watterson et al, 2013).…”
Section: Perception Of Speechmentioning
confidence: 99%
“…In one study, 35% of the children with clefts reported that they often/very often had to repeat a verbal message due to reduced speech intelligibility, but nevertheless 91% were satisfied with their speech (Van Lierde et al, 2012). Subjective perceptions of speech have also been related to social acceptance (Watterson et al, 2013).…”
Section: Perception Of Speechmentioning
confidence: 99%
“…Na perspectiva psicológica, situações de estresse comumente são relatadas em pesquisas com essa população, como a insatisfação com a aparência 8 e o receio de ser alvo de zombaria ou ser avaliado negativamente por outras pessoas pela deformidade ou pela voz 9,10 . Considerando as possíveis situações estressantes vivenciadas por essa população, entende-se que é importante identificar como ocorre o enfrentamento dos principais estressores de pré-adolescentes em tratamento de FLP.…”
Section: Introductionunclassified